MATERNAL AND FETAL OUTCOMES IN POST-KIDNEY TRANSPLANT PREGNANCIES: A MANAGEMENT PERSPECTIVE - Babazhanova N.U., Nadirkhanova N.S. (Central Asian Journal of Medicine, 2025)
Pregnancy in kidney transplant recipients presents complex clinical challenges requiring multidisciplinary management. This retrospective analysis evaluates pregnancy outcomes in 20 women with functioning renal transplants, monitored between 2012 and 2025. The majority delivered at term, with 45% undergoing cesarean section and 55% experiencing spontaneous vaginal delivery. Clinical management included regular monitoring of renal function, immunosuppressive therapy, and obstetric evaluation. Immunosuppressive regimens—primarily low-dose tacrolimus, azathioprine, and prednisolone—were well tolerated. Stable renal function and positive maternal-fetal outcomes were observed when medical recommendations were consistently followed. Preterm delivery occurred in 15% of cases, typically associated with hypertensive disorders and placental insufficiency. The findings underscore the importance of individualized, protocol-driven prenatal care by a dedicated team of transplantologists, nephrologists, and obstetricians to optimize safety for both mother and child. The article describes the characteristics of pregnancy in women after kidney transplantation and the obtained results.